Proteomic study revealed antipsychotics-induced nuclear protein regulations in B35 cells are similar to the regulations in C6 cells and rat cortex - Tinchou Li; Mingcheng Lee; Fuming Tsai; Yunhsiang Chen; Yiyin Lin; Maoliang Chen (BMC, 2018)
Abstract Background Based on accumulating evidence, the regulation of protein expression by antipsychotic drugs (APDs) might be closely related to the control of psychotic symptoms when these drugs are used to treat mental disorders. The low quantity of nuclear proteins in the cell hinders their detection because signal for rare proteins are masked in most proteomic detection systems. Methods Nuclear proteins fractionated from APD-treated B35 cells were labeled with iTRAQ and detected by LC/MS/MS to investigate APD-induced alterations in nuclear protein expression. Western blot, immunofluorescent cell staining, and immunohistochemical staining were applied to validate the findings. Results The expression of ADP/ATP translocase 2, heat shock cognate 71 kDa protein, histone H1.2, histone H3.3, histone H4, non-POU domain-containing octamer-binding protein, nucleolin, nucleophosmin, prelamin-A/C, plectin-1, vimentin, and 40S ribosomal protein S3a was regulated by APDs in B35 cells, according to our proteomic data. According to the results of the gene ontology analysis, all these proteins played important roles in biological processes or in molecular functions in cells. Western blot results showing APD-induced alterations in nuclear protein expression in B35 cells were consistent with the LC/MS/MS results. Heat shock cognate 71 kDa protein and vimentin expression in C6 cells were not affected by the three APDs. As shown in the immunofluorescent cell staining, all the three APDs altered protein expression to similar extents. We also examined whether the expression of these proteins was affected by APDs in the prefrontal cortex of rats administered sub-chronic and chronic APD treatments by western blotting and immunohistochemical staining. Conclusions The findings of the proteomic analysis of APD-treated B35 cells were recapitulated in the APD-treated rat cortex. The expression of some proteins was altered by APDs in rat prefrontal cortex in a time-dependent manner.